Prevalence and Associated Factors of Loneliness Among Older Adults in Indonesia: Insights from the Indonesian Family Life Survey (IFLS-5) - Asri, Yuni; Hartono , Aris; Murwani , Arita; Julia Kristiarini , Juda; B. Manga , Yankuba (Jurnal Ners, 2025)
Introduction: Loneliness presents a significant threat to the mental and physical health of older adults in Indonesia, constituting a pressing public health concern. The study aims to determine the prevalence of loneliness and identify the factors associated with loneliness among older adults in Indonesia. Methods: A cross-sectional analysis was conducted using data from the fifth wave of the Indonesian Family Life Survey (IFLS-5). Sociodemographic, loneliness, and health-related variables were examined through multivariate logistic regression to identify factors associated with loneliness. Results: High levels of loneliness were reported by 11.2% of participants, while 88.8% experienced low levels. Significant factors included lower educational attainment (adjusted odds ratio [AOR] = 2.05, 95% confidence interval [CI] = 1.43–2.93, p < 0.001), life dissatisfaction (AOR = 1.55, 95% CI = 1.16–2.06, p = 0.003), and poor sleep quality (AOR = 2.32, 95% CI: 1.72–3.39, p < 0.001). Geographic location also emerged as a significant factor; participants residing in Sumatra were less likely to report loneliness (AOR = 0.64, 95% CI = 0.42–0.99, p = 0.049). Other variables, such as self-rated health, chronic conditions, religious participation, and cell phone ownership, showed significance in unadjusted models but were no longer statistically significant after adjustments were made. Conclusion: The findings underscore the necessity for targeted interventions to mitigate loneliness among older adults in Indonesia. Such interventions should focus on improving health, enhancing social support, and fostering connectivity, with the aim of elevating the quality of life and alleviating loneliness within this vulnerable population.